Physical and chemical characterization of technogenic pozzolans for the application in blended cements. (30th January 2018) - Záleská, Martina; Pavlíková, Milena; Pavlík, Zbyšek; Jankovský, Ondřej; Pokorný, Jaroslav; Tydlitát, Vratislav; Svora, Petr; Černý, Robert
Graphical abstract: Highlights: System of physical and chemical techniques for assessment of technogenic pozzolans. Physical and chemical prerequisites, reactivity, performance in blended cements. Evaluation of synergistic calorific effects. Pozzolan effectiveness coefficient as a new criterion. Practical application demonstrated for fly ash from a coal power plant. Abstract: Technogenic pozzolans present a diverse group of materials. They differ in their origin, chemical and mineralogical composition, granulometry, or amorphous content. However, the analysis of their properties before utilization as supplementary cementitious materials is often insufficient which may lead to unexpected results in some cases. In this paper, a system of physical and chemical techniques for the characterization of technogenic pozzolans is proposed, which takes into account both functional and environmental aspects. The system is hierarchical and consists of three sets of methods which assess consecutively the fundamental physical and chemical prerequisites, reactivity, and performance in a blend with Portland cement. The practical application of the methodology is demonstrated for the example of fly ash from a coal power plant as the most common technogenic pozzolan. Experimental results show that the proposed system has good prerequisites to serve as a good guidance for both research and building practice.